STRATEGI KOMUNIKASI TOKOH AGAMA DALAM PERCEPATAN PENURUNAN STUNTING DI KABUPATEN PASAMAN BARAT - Ikrar Fajri (ADISAM PUBLISHER, 2024)
The research results show that: (1). Supporting and inhibiting factors for religious figures' communication are: first, use of language (semantics), second, psychology, third, technical, fourth, environment, fifth, media, sixth, time, seventh, image, but there are a few personal obstacles that come from the communicant themselves so that they become a factor inhibiting communication. carried out by religious figures. (2). The communication strategy of religious figures in accelerating stunting reduction is: first, getting to know the audience, second determining the message, third determining the method, fourth selecting and using media. From the results of the research conducted by the author, the author can conclude that the communication strategy used by religious figures in the process of accelerating stunting reduction is very good because religious figures are able to maximize various components and indicators of existing communication strategies, so that they can be accepted by the community, students and catin